Arginine dipeptides affect insulin aggregation in a pH‐ and ionic strength‐dependent manner. Issue 3 (25th February 2015) - Nuhu, Mariam M.; Curtis, Robin
Abstract Solutions containing arginine or mixtures of arginine and other amino acids are commonly used for protein liquid formulations to overcome problems such as high viscosities, aggregation, and phase separation. The aim of this work is to examine whether the stabilizing properties of arginine can be improved by incorporating the amino acid into a dipeptide. A series of arginine‐containing dipeptides have been tested for their ability to suppress insulin aggregation over a range of pH and ionic strength. The aggregation is monitored at room temperature using a combination of turbidimetry and light scattering for solutions at pH 5.5 or 3.7, whereas thermal‐induced aggregation is measured at pH 7.5. In addition, intrinsic fluorescence has been used to quantify additive binding to insulin. The dipeptide diArg is the most effective additive in solutions at pH 5.5 and 3.7, whereas the dipeptide Arg‐Phe almost completely eliminates thermally‐induced aggregation of insulin at pH 7.5 up to temperature of 90°C. Insulin has been chosen as a model system because the molecular forces controlling its aggregation are well known. From this understanding, we are able to provide a molecular basis for how the various dipeptides affect insulin aggregation.